Optimizing library catalogue management using object-oriented e-catalogue application: A case study at Universitas Muhammadiyah Jambi - Saleh Yaakub; Ika Safitri Windiarti; Wawan Joko Pranoto (Researcher and Lecturer Society, 2025)
The development of a comprehensive and efficient library catalogue system is essential for improving accessibility to information in modern educational environments. This research addresses the inefficiencies of manual cataloguing methods at Universitas Muhammadiyah Jambi’s library by proposing an Object-Oriented Programming (OOP)-based E- catalogue system. The system, developed using Visual Basic and Microsoft Access, streamlines the book-searching process, enhancing user access to book details such as authors, titles, and synopses. The system’s user-friendly interface supports features like search, administration, and data backup, improving both search efficiency and user satisfaction. This research contributes to the advancement of library management systems, demonstrating the potential of OOP-based design for future applications in similar academic institutions. Future research can build on this work by integrating machine learning techniques for personalized book recommendations and expanding the system's scalability.